Magnetic behavior identification of high-purity hematite (Fe2O3) extracted from iron ore by co-precipitation method - Fauzi Fauzi; Adi Rahwanto; Malahayati Malahayati; M. Nizar Machmud; Zulkarnain Jalil (Department of Physics, Sebelas Maret University, 2025)
Magnetic mineral identification was successfully carried out on the iron ore from Manggamat in South Aceh Regency, Indonesia. This initial study was conducted in an attempt to increase the added value of local minerals. This study was performed by using co-precipitation method combined with mechanical milling and analyzed using X-ray diffraction and fluorescence (XRD, XRF) and the magnetic properties evaluated by Permagraph. These investigations indicate that the dominant phase in the Manggamat iron ore is hematite (Fe2O3), showed a content of 85.31%, followed by SiO2 compounds (11.01%), and the lowest concentration was SnO2 (0.02 %). Furthermore, observation of the magnetic properties showed that the magnetic saturation (Ms) of 0.1 Tesla, then residual magnetization or remanent (Br) of 0.017 Tesla, and a reverse magnetic field or coercivity (Hc) of 12.39 kA/m. As the milling time increased, the magnetic saturation and remanent field decreased, whereas the coercive field increased. This characteristic is known as the superparamagnetic behavior which widely used in biomedical application.